Morphological and structural variations in anodic films grown on polished and electropolished titanium substrates - Da Silva Palma, Dener Pedro [UNESP]; Nakazato, Roberto Zenhei [UNESP]; Codaro, Eduardo Norberto [UNESP]; Acciari, Heloisa Andréa [UNESP] (FapUNIFESP (SciELO), 2019)
The objective of this work was to investigate the effects of anodization parameters on the anatase phase formation of titanium oxide films, which have been grown on both electropolished and nonelectropolished titanium surfaces by direct current anodization in 0.25 and 2.5 mol L-1 H3PO4 solutions, respectively, at three anodization times (3, 6 and 12 hours). SEM, Raman spectroscopy and X-ray diffraction techniques revealed the characteristics of anodic films. Films were characterized according to presence of crystalline nuclei of anatase phase on an amorphous matrix. It was found that differences in size, shape and distribution of crystalline grains on anodized surfaces are affected by the type of polishing given to substrates. The particles on electropolished surfaces were grown in well-defined layers following cone-shaped grains. On the other hand, the crystallization phenomenon on nonelectropolished substrates has led to the appearance of smaller particle sizes and a larger number of particles distributed along the surface as well.
Keywords: Anatase; Anodization; Electropolishing; Titanium